Tobacco use disorder in patients with other mental disorders: a dual disorder perspective from clinical neuroscience - Szerman, Nestor; Parro, Carlos; Vega, Pablo; Basurte-Villamor, Ignacio; Ruiz-Veguilla, Miguel (Frontiers in Psychiatry, 2024)
Tobacco smoking is the leading cause of disability and preventable deaths worldwide, but it should be differentiated from tobacco use disorder, which is, according to the Diagnostic and Statistical Manual of Mental Disorders, a bona fide mental disorder. The rapid delivery of nicotine to the brain activates acetylcholine receptors and stimulates the release of dopamine, both systems implicated in other mental disorders. Rates of tobacco use disorder are much higher among people suffering from other mental disorders and these patients find it more difficult to quit. Dual disorders, from a transdiagnostic perspective, identify patients with substance use disorder, in this case tobacco use disorder, and other mental disorders. A dual disorder is a complex clinical condition that is often underdiagnosed, undertreated, and difficult to manage. Appropriate and integrated tobacco use disorder treatment programs for people also suffering from other mental disorders could improve outcomes. Bio-psycho-social approaches to tobacco use disorder include specific biological treatments (e.g., bupropion, varenicline, cytisine, nicotine replacement therapy or deep trans-magnetic stimulation). However, these treatments don’t have the same outcomes in patients with dual disorders. Therefore, as in other dual disorders, harm reduction measures, such as vaping nicotine through electronic cigarettes or tobacco replacement therapies should be considered as alternative tools for dual tobacco use disorder management. These clinical considerations emerge from a narrative literature review and expert consensus and will specifically address considerations for changes in clinical practice to improve the treatment of tobacco use disorder and other mental disorders.